NUCLEAR ENERGY: PROBLEM OR SOLUTION FOR THE BRAZILIAN ELECTRICITY SECTOR? - Martins, Gustavo Henrique Ferrari; Vieira, Gilberto (Seven Editora, 2026)
The present article explores nuclear energy in the context of the Brazilian electrical system, beginning with a global overview that highlights the importance of this energy source in the global energy matrix, emphasizing its crucial role in diversifying energy sources and mitigating carbon emissions. The study also examines this global perspective and the specific situation in Brazil, where the contribution of nuclear energy remains modest. Furthermore, the inherent qualities of this source are noted, such as its energy density and its capacity to provide a continuous and reliable energy supply. Additionally, the associated benefits are analyzed, including the reduction of dependence on fossil fuels and the decrease in greenhouse gas emissions. However, the risks involved are also addressed, such as the management of radioactive waste and the potential for nuclear accidents. Thus, there is a balance observed between the qualities and potential risks of this alternative, enabling the implementation of strategies to ensure energy security within the Brazilian electrical system.